THE EFFECT OF USING COLLABORATIVE STRATEGIC READING (CSR) ON STUDENTS’ READING COMPREHENSION - Rotua Parsaulian Aritonang; Ashari P. Swondo (Universitas Potensi Utama, 2021)
The objective of this study was to find out The Effect of Using Collaborative Strategic Reading (CSR) on Students’ Reading Comprehension On Narrative Texts’at the Nine grade students’ of SMP Swasta Harvard Martubung. The sample of this study was the Nine grade students’ of SMP Swasta Harvard Martubung. They were class IXA as the experimental class and class IXB as the control class. Each class consisted of 25 students, with 9 male students and 16 female students. The method used in this study was a quantitative method. The instruments of this study were tests. For sampling technique, the writer used purposive sampling. In addition, to the calculation of the data, the writer used SPSS 20 for calculation of this study. The result of the study was that post-test mean score of control class was 77,12, while post-test mean score of experimental class was 84,96. It means that the effect of treatment was strong. Based on the result of quantitative data, CSR Strategy had helped the students in four things; to make easier students’ reading comprehension, toincrease students’ curiosity of the content of passage, to increase students’ ability in using one of higher order of thinking skill (connecting), and to enrich students’ vocabulary. In short, it means that the use of CSR strategy had significant effect to the students’ reading comprehension.